Higher than expected N2O emissions from soybean crops in the Pampas Region of Argentina: Estimates from DayCent simulations and field measurements - Della Chiesa, Tomas (2022)
In developing countries, agriculture generally represents a large fraction of GHG emissions reported in National Inventories, and emissions are typically estimated using Tier 1 IPCC guidelines. However, field data and locally adapted simulation models can improve the accuracy of IPCC estimations. In this study we aimed to quantify anthropogenic N2O emissions from croplands of Argentina through field measurements, model simulations and IPCC guidelines. We measured N2O emissions and their controlling factors in 62 plots of the Pampas Region with corn, soybean and wheat/soybean crops and in unmanaged grasslands. We accounted for gross emissions from crops and background emissions from unmanaged grasslands to calculate net anthropogenic emissions from crops as the difference between them. We calibrated and evaluated the DayCent model and then simulated different weather and management scenarios. Finally, we applied IPCC guidelines to estimate anthropogenic N2O emissions at the same plots. The DayCent model accurately simulated annual N2O emission for all crops as compared to measured data (RMSE = 1.4 g N ha−1 day−1). Measured and simulated emissions in soybean crops were higher than in corn and wheat/soybean crops. Gross N2O emissions ranged from 1.4 to 5.1 kg N ha−1 yr−1 for current environmental (soil and weather) and management (crops and fertilizer doses) conditions. Background emissions ranged between 1.1 and 1.3 kg N ha−1 yr−1, and therefore net anthropogenic emissions ranged from 0.3 to 4.0 kg N ha−1 yr−1. IPCC Tier 1 emission factors underestimated N2O releases from soybean, that were on average 4.87 times greater when estimated with DayCent and observations (0.53 vs 2.47 and 2.69 kg N ha−1 yr−1, respectively). On the contrary, IPCC estimates for corn and wheat/soybean crops were similar to modeled and measured values. Our results suggest that N2O emissions from the vast 15 million ha of soybean croplands in the Pampas Region may be substantially underestimated.